Alleviation of Antioxidant Defense System by Ozonized Olive Oil in DNBS-Induced Colitis in Rats. (3rd September 2014) - Abu-Gharbieh, Eman; Bayoumi, Fatehia A.; Ahmed, Naglaa G.
Abstract : The aim of the study was to evaluate the potential protective effect of ozonized olive oil (OZO) in 2, 4-dinitrobenzene sulphuric acid (DNBS) induced colitis in rats and to elucidate the role of some antioxidant defense system (superoxide dismutase "SOD, " glutathione peroxidase "GSH-Px, " and catalase "CAT") in these effects. The physicochemical parameters including viscosity, peroxide, and acid values of olive oil and OZO were evaluated. The animals were divided into several groups and the colitis was induced in the rats by intracolonic instillation of DNBS at dose of 15 mg/rat. Olive oil (OO) at dose of 6 mg/kg and OZO at doses of 3 and 6 mg/kg was administered orally for 7 days, starting the day before induction of colitis. Our results showed that macroscopic and microscopic damage scores were significantly reduced in a dose response manner in rats pretreated with OZO only. In contrast, CAT, GSH-Px, and SOD activities were significantly increased in the distal colon of inflamed animals pretreated with OZO with respect to control group dose dependently. Results demonstrate that OZO pretreatment exerts protective effects in DNBS induced colitis in rats and provide evidence that the protective effects of OZO are mediated by stimulation of some antioxidant enzymes.